Efficacy test of a Mycoplasma hyorhinis mRNA-LNP vaccine candidate - Eszter Zsófia Nagy; Levente Szeredi; Hiromi Muramatsu; Noémi Nagy; Dénes Grózner; Zsuzsa Kreizinger; Kinga M. Sulyok; Bandana Pangabam; Lilla Tóth; Rachel H.J. Jun; Dorottya Földi; Enikő Wehmann; et al. (Vaccine: X)
Background: Mycoplasma (M.) hyorhinis is a widespread bacterium that frequently causes polyserositis and arthritis in post-weaning pigs. Currently, prevention and treatment strategies rely on mitigating risk factors and administering antibiotics, as no vaccines are commercially available in Europe. Developing a safe and efficacious vaccine could provide a long-term solution, reducing the economic impact of M. hyorhinis infections. Therefore, the present study aimed to develop a M. hyorhinis mRNA-LNP vaccine candidate. Materials and methods: The selected antigens were highly conserved proteins involved in bacterial adhesion. The mRNAs encoding these proteins were produced using established protocols and subsequently encapsulated in lipid nanoparticles through a self-assembly technique. For the in vivo efficacy assessment, three-week-old piglets were immunized with the candidate vaccine, and the injection site was monitored daily. At six weeks of age, the animals were challenged intravenously on two consecutive days. The clinical examinations were performed daily, while blood samples were collected weekly for a M. hyorhinis-specific antibody ELISA and Porcine Interferon gamma (Porcine IFN-γ) ELISA. Three weeks post-challenge, the animals were euthanized for gross and histopathological examinations. Additionally, body temperatures were recorded daily, and the body weights of the animals were measured upon arrival and then at six and nine weeks of age. Results: After the challenge, the vaccinated group showed significantly higher IgG antibody titers than the positive control. Similarly, the vaccinated group's average daily weight gain was higher than the one of the challenge group. However, the vaccine candidate failed to confer sufficient protection against the clinical signs, pathological and histopathological lesions. Discussion: Overall, a single dose of mRNA-LNP vaccine candidate was ineffective in preventing the disease caused by M. hyorhinis. Future research should focus on optimizing the vaccine formulation by incorporating additional antigens or adjuvants, implementing a two-dose immunization, or exploring alternative routes of administration.